2013
DOI: 10.1007/s00251-013-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of MICB diversity in the Zhejiang Han population: PCR sequence-based typing for exons 2–6 and identification of five novel MICB alleles

Abstract: The polymorphism of major histocompatibility complex class I chain-related gene B (MICB) and variations in MICB alleles in a variety of populations have been characterized using several genotyping approaches. In the present study, a novel polymerase chain reaction sequence-based typing (PCR-SBT) method was established for the genotyping of MICB exons 2-6, and the allelic frequency of MICB in the Zhejiang Han population was investigated. Among 400 unrelated healthy Han individuals from Zhejiang Province, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Compared to MICA locus, MICB allelic distribution has been less thoroughly investigated in worldwide populations [6]. Our data showed that similar to Chinese Han populations and European Caucasian populations studied [6,[13][14][15][16], MICA*008:01 and MICB*005:02 were the most common alleles in this population. Peculiarities in MICA allelic profile were observed in this population, for example this population had a relatively high frequency of MICA gene deletion (5.7%).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Compared to MICA locus, MICB allelic distribution has been less thoroughly investigated in worldwide populations [6]. Our data showed that similar to Chinese Han populations and European Caucasian populations studied [6,[13][14][15][16], MICA*008:01 and MICB*005:02 were the most common alleles in this population. Peculiarities in MICA allelic profile were observed in this population, for example this population had a relatively high frequency of MICA gene deletion (5.7%).…”
Section: Discussionmentioning
confidence: 54%
“…Nowadays most Chinese Mongolians inhabit the Inner Mongolia autonomous region, the third largest subdivision of China covering about 12.3% of the country's territory, where Mongols are the second largest ethnic group comprising about 17% (approximately 4 million) of the population. Data on MICA and MICB polymorphisms and their linkage disequilibrium (LD) with HLA-B in different Chinese Han populations are accumulating [13][14][15][16]; nevertheless, such information is still lacking for the Chinese Mongolian population. In this study, we investigated MICA and MICB polymorphisms as well as their LD with HLA-B in a Chinese Mongolian population.…”
mentioning
confidence: 99%
“…There are currently 40 MICB alleles listed in the April 2014 IMGT/HLA Database release . Among these, MICB*005:02 is the most frequent in several populations (35%–65%) followed by MICB*004:01 (12%–26%), MICB*002:01 (11%–16%) and MICB*008 (6%–15%) . MICB allele typing of exons 2–6 by SBT revealed 10 different alleles from 38 IHW cell line DNA samples.…”
Section: Resultsmentioning
confidence: 99%
“…Exon 1 is not included due to an extremely long intron 1 sequence that would render the fragment too large for regular genomic polymerase chain reaction (PCR) amplification. Exons 2–6 of the MICB gene were amplified and sequenced using the methods described by Ying et al and Field et al using primers listed in Table S1. Allele level assignment (excluding intron variants) of MICB alleles was achieved in all cases using Assign SBT™ as above.…”
Section: Methodsmentioning
confidence: 99%
“…There, the allele MICB * 005 is the most common allele with frequencies of over 50%. It is followed by MICB * 002 and MICB * 004 with frequencies over 10% and MICB * 008 and the null allele MICB * 009N with frequencies over 5% (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%